INFLUENCE OF VARIETY FEATURES OF SMOOTH BROMEGRASS SELECTION SAMPLES ON GRASS STAND DURABILITY AND YIELD - Marinich, L. H.; Barabolia, O. V.; Kavalir, L. V. (Scientific Progress & Innovations, 2021)
One of the valuable fodder species of grasses is smooth brome grass. Smooth brome grass plants are rich in protein – up to 15 %, fats – 19.7–24.9 %, cellulose – up to 8 %. Its main feature is that the green material and hay are rich in sugars and minerals such as phosphorus, calcium, potassium, sulfur, and magnesium. One of the modern problems in the selection of smooth brome grass is the creation of varieties, which would be characterized by adaptability to certain soil and climatic conditions, high fodder productivity, improved quality indicators, seed yield, and durability. At present, 14 registered varieties of smooth brome grass are cultivated in different soil and climatic conditions of Ukraine. But these varieties do not fully meet the pro-duction requirements, so there is a need for selective improvement of this crop. The purpose of the research was to identify the dynamics of fodder productivity formation to determine the variety characteristics of smooth brome grass selection material. Field and quantitative methods, the method of test sheaf, weight, and statistical were used in the course of researches. 0107, 0110, 0752, 1005 and 1002 samples belong to hay-making type, and they are characterized by maximum productivity during the first 3 years of using. It is the best to use such samples for short-term application in field crop rotations; 1007, 1006 and 1071samples be-long to haymaking and pasture type. They are characterized by the average productivity during the first 3 years of cultivation (29–38 t/ha) and the average level of reducing green material yield on the 7th year of application (45–61 %). It is expedient to use these samples in fodder crop rotations for 5–7 years; 1012, 1008 and 1003 samples belong to pasture type. They are characterized by low productivity in the first 3 years of cultivation (20–26 t/ha) and slowly reduce the yield of green material (35–45 %) on the 7th year of using. It is better to use them for pastures, reclamation of eroded lands and as lawn crops.